Studying and mapping the landscapes of the Sareptsky peninsula in Lower Volga, Russia - O. Yu. Kosheleva; S. S. Shinkarenko; D. A. Solodovnikov; R. S. Omarov (Юг России: экология, развитие)
Aim. Islands and peninsulas in the Volga are of great environmental and recreational importance for the Volgograd agglomeration. Identifying the current state of geocomplexes in the Sareptsky peninsula allow us to assess the developmental trends of the floodplain ecosystems in the Lower Volga, which are under intense economic pressures.Material and Methods. The mapping was done by decoding Sentinel-2 satellite imagery and drawing landscape contours using the QGIS program. Field work was carried out in June 2019. Seven test plots were laid out. Inventory of forest plantations was undertaken with distribution of trees according to condition and a geobotanical description of the grass stand was done.Results. The Sareptsky peninsula was revealed to be an island by origin that was artificially attached to the native coast. The landscape structure of the peninsula includes 6 natural-anthropogenic complexes, of which the largest area (62.9%) is occupied by natural floodplain forest and cultivated forest. 13.9% is occupied by water meadows of the central floodplain, 8.0% by aquatic complexes of inland water bodies, 7.3% by anthropogenically transformed areas (settlements and industrial lands, roads and hydraulic structures), 5.1% by open areas of fresh-water floodplain and 2.8% by beach shoals of the river channel floodplain. The signs were revealed of a negative effect on the Volga through the regulation of its flow from desiccation of poplars and meagre species composition of meadow vegetation. It was established that the territory of the peninsula is exposed to a small extent by recreational activities.Conclusion. Landscape-ecological studies made in the Sareptsky peninsula allowed the assessment of the current state of forest and meadow ecosystems, the identification of the principal factors involved in the deterioration of their ecological status and the articulation of a better way to optimize nature management.